The Representation Of Obsessive-Compulsive Personality Disorder Across The Characters In The Anthology Film The House (2022) - Caesar Danuarta; Putri Ayienda Dinanti (CV. SINAR HOWUHOWU, 2026)
Films have become an important medium for representing psychological disorders, enabling audiences to gain a deeper understanding of mental health through fictional characters. Integrating psychological perspectives into film analysis also strengthens the interdisciplinary relationship between psychology, literature, and cinema. Therefore, this study aims to analyze the representation of Obsessive-Compulsive Personality Disorder (OCPD) through the three main characters in the stop-motion animated anthology film The House (2022). This study employed a qualitative descriptive method using the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) as the analytical framework. The primary data were obtained from the film, while supporting data were collected from books, journal articles, and psychological references related to OCPD. Data were gathered through repeated viewing, observation, and categorization of scenes, dialogues, and character actions based on the DSM-5 diagnostic criteria. The findings reveal that Raymond, the Developer, and Rosa collectively represent four OCPD symptoms: preoccupation with details, perfectionism that interferes with task completion, excessive devotion to work and productivity, and rigidity and stubbornness. Rather than portraying the disorder through a single character, the film distributes these symptoms across multiple narratives, illustrating a distinctive representation of OCPD in an anthology film. This study contributes to a more critical and empathetic understanding of psychological disorders in literary and cinematic studies.